Beauty is more than skin deep: a non‐invasive protocol for in vivo anatomical study using micro‐CT. Issue 3 (20th October 2016) - Broeckhoven, Chris; du Plessis, Anton; le Roux, Stephan Gerhard; Mouton, Pieter le Fras Nortier; Hui, Cang
Summary: Microcomputed tomography (μCT) is a widely used tool in biomedical research, employed to investigate tissues and bone structures of small mammals in vivo . The application of in vivo μCT scanning in non‐medical studies greatly lags behind the rapid advancements made in the biomedical field wherein the methodology has evolved to allow for longitudinal studies and eliminate the need to sacrifice the animal. Ecological and evolutionary studies often involve morphological measurements of a large sample of live animals; however, the potential of in vivo μCT imaging as a method for data acquisition has yet to be delineated. Here, we describe a protocol for in vivo μCT imaging of the internal anatomy of reptiles and amphibians, commonly used study organisms in ecological and evolutionary research. We consider the skeletal and extraskeletal (i.e. osteoderms) bones of a lizard as a case study to elucidate the potential of in vivo μCT imaging. First, we explore the effects of various parameter settings on radiation dose, scan time and image quality. Secondly, we develop a protocol to immobilize and restrain study organisms during scanning without need for the administration of anaesthetics and compare the results of the in vivo protocol to images obtained post‐mortem . To immobilize animals, we replace the use of anaesthetics by cooling, thereby allowing the use of previously unsuitable rotating gantry μCT scanners that are readily available in scientific institutions. The resultant image quality of in vivo μCT scans is similar to that of post‐mortem μCT scans, especially in the abdominal region. We discuss the effect of tube voltage, distance to X‐ray source and metal filtration on radiation dose, and how these parameters could be altered to reduce the cumulative radiation dose while maintaining optimal image quality. The proposed in vivo μCT protocol offers a new approach to acquire anatomical information for non‐biomedical studies. We offer specific suggestions as to how the protocol can be employed to suit a variety of model organisms.